Teaching Reading through Short Stories Towards Students’ Reading Improvement and Perceptions at SMAN 9 Makassar - Putra, Diftah Cahyana; Atmowardoyo, Haryanto; Talib, Ahmad (Journal of Excellence in English Language Education, 2024)
This study aims to determine whether the use of short stories in learning to read improves students' reading comprehension or not, as well as to find out how students perceive the use of short stories in an effort to improve students' reading comprehension. This study uses quantitative methods to determine whether or not students' reading comprehension increases after using short stories in the teaching and learning process, and to determine students' perceptions of the use of short stories. The researcher took the research subjects of class XI MIA 3 SMAN 9 Makassar students in the 2020/2021 school year, totaling 30 students with a hybrid learning system of 15 students. Instruments in data collection are tests, observations and questionnaires. The results of the data analysis show that the use of short stories can improve students' reading comprehension. This is evident from the results of the analysis of students' pre-test and post-test scores, where the average pre-test score of students is 60 and the average post-test score of students increases to 83. Thus, it can be concluded that by using short stories the value of the average student increased 38.3%. In addition, based on the results of the questionnaire distributed to students, shows that students have a positive perception of the use of short stories in the teaching and learning process of reading in the classroom. This can be seen from the average score of the overall perception of students is 50.9, where this score has passed the limit of the average score for perceptions considered negative, which is equal to or less than 49.